The tricot approach. Guide for large-scale participatory experiments - Etten, Jacob van; Manners, Rhys; Steinke, Jonathan; Matthus, Elsa; Sousa, Kauê de (Bioversity International and the International Center for Tropical Agriculture, 2020)
Triadic comparison of technology options (tricot) is a research methodology that helps farmers to identify the most suitable technologies for the local conditions of their farm. Tricot (read: ‘try-cot’) engages farmers as ‘farmer researchers’ in the testing or validation of new crop varieties and other promising technologies. Tricot is supported by the ClimMob digital platform (https://climmob.net). This guide provides an introduction to tricot and each of the steps in the experimental cycle.